The Influence of Security, Easy, Benefits and Community Interest on The Use of Digital Payment as A Payment Tool in Jabodetabek - Justin, Justin; Yani Kusumastuti, Sri (International Journal of Social Science, Education, Communication and Economics, 2022)
This study aims to analyze and test the variables of security, convenience, usefulness and public interest in the use of digital payment as a means of payment in Jabodetabek. This Study uses a qualitative method with purposive sampling technique. The population in this study is the user community of application-based digital payments such as DANA, GOPAY, OVO, SHOPEEPAY, SAKUKU, ISAKU, PAYTREN, DOKU, and LINKAJA. The number of samples is 233 respondents. The analysis method is a structural equation model. The result of this study show that security and public interest have a significant effect on the use of digital payments as a means of payment and for convenience and usefulness are not a benchmark for the community, especially at this time the impact of behavior who are used to make payments using digital payments.